2009
DOI: 10.1007/s11517-009-0525-1
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of human electroencephalographic activity caused by multiple extremely low frequency magnetic field exposures

Abstract: In the past, many studies have claimed that extremely low frequency (ELF) magnetic field (MF) exposures could alter the human electroencephalographic (EEG) activity. This study aims at extending our ELF pilot study to investigate whether MF exposures at ELF in series from 50, 16.66, 13, 10, 8.33 to 4 Hz could alter relative power within the corresponding EEG bands. 33 human subjects were tested under a double-blind and counter-balanced conditions. The multiple repeated three-way analysis of variance (ANOVA) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…This can induce measurable changes in electrical brain activity and influence neuronal functions such as motor control, sensory perception, and cognitive activities. In healthy humans, Bell et al (1994) compared the effects of 1.5 and 10 Hz MF, while Cvetkovic and Cosic (2009) analyzed the effects of several ELF-MF frequencies (4, 8.33, 10, 13, 16.6 and 50 Hz) on the power of the corresponding EEG bands. In both cases, spectral analysis demonstrated that specific EEG frequencies can be influenced by stimulation at matching MF frequencies.…”
Section: Nibs Modulation Of Oscillatory Activitiesmentioning
confidence: 99%
“…This can induce measurable changes in electrical brain activity and influence neuronal functions such as motor control, sensory perception, and cognitive activities. In healthy humans, Bell et al (1994) compared the effects of 1.5 and 10 Hz MF, while Cvetkovic and Cosic (2009) analyzed the effects of several ELF-MF frequencies (4, 8.33, 10, 13, 16.6 and 50 Hz) on the power of the corresponding EEG bands. In both cases, spectral analysis demonstrated that specific EEG frequencies can be influenced by stimulation at matching MF frequencies.…”
Section: Nibs Modulation Of Oscillatory Activitiesmentioning
confidence: 99%
“…25,33,34 Many of the studies from 1985 to 2005, gathered in a review article, illustrated the effect of the use of large spread spectrum of PEMF doses on decreasing headache activity. 17 Although most of these research studies had no control or comparison group, or had very brief follow-up periods and uncompleted reports of dosimeter.…”
Section: Discussionmentioning
confidence: 99%
“…11,37 On the other hand, an electromagnetic field with a frequency of 10 Hz reduced the alpha band of the EEG. 25,38,39 There are some controversies regarding the effect of PEMF due to the intensity and frequency of exposure on EEG. 24,38,39 Then the electrophysiological rationale of effect of electromagnetic field on migraine may be supported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies indicated that exposure to low-frequency magnetic fields is able to alter basic neural function in rats (Lovely et al, 1993;Lyskov et al, 1996;Thomas et al, 1986;Welker et al, 1983;Zhadin et al, 1999), effects that have in part been explained in terms of changes in the glutamate receptor N-methyl-D-aspartate (Flohr, 2000;Frilot et al, 2014). A variety of other reports (Cvetkovic and Cosic, 2009;Vorobyov et al, 1997Vorobyov et al, , 1998Vorobyov et al, , 2010 have linked weak ELF magnetic field exposure to changes in the EEG, to electrical activity in the brain (Marino et al, 2004) and to neuroendocrine receptors (Janac et al, 2009). One critically important addition to this body of research (Zhadin et al, 1998) established that the conductivity of glutamic acid in solution increases sharply at remarkably small magnetic field levels (~40 nT) when these fields are applied at ion cyclotron resonance field combinations, a result independently replicated in three other laboratories (Alberto et al, 2008;Comisso et al, 2006;Pazur, 2004).…”
Section: Introductionmentioning
confidence: 99%